Comparative transcriptomics reveal different genetic adaptations of biofilm formation in Bacillus subtilis isolate 1JN2 in response to Cd2+ treatment - Yang, Wei; Yan, Haixia; Dong, Guanghui; Li, Zhengpeng; Jiang, Chunhao; Gu, Dalu; Niu, Dongdong; Zhou, Danni; Luo, Yuming (Frontiers in Microbiology, 2022)
Biofilm plays important roles in the life cycle of Bacillus species, such as promoting host and object surface colonization and resisting heavy metal stress. This study utilized transcriptomics to evaluate the impacts of cadmium on the components, morphology, and function of biofilms of Bacillus subtilis strain 1JN2. Under cadmium ion stress, the morphology of the B. subtilis 1JN2 biofilm was flattened, and its mobility increased. Moreover, differential gene expression analysis showed that the main regulator of biofilm formation, Spo0A, decreased in expression under cadmium ion stress, thereby inhibiting extracellular polysaccharide synthesis through the SinI/SinR two-component regulatory system and the AbrB pathway. Cadmium ion treatment also increased the SigD content significantly, thereby increasing the expression of the flagella encoding and assembly genes in the strain. This promoted poly-γ-glutamic acid production via the DegS/DegU two-component regulatory system and the conversion of biofilm extracellular polysaccharide to poly-γ-glutamic acid. This conferred cadmium stress tolerance in the strain. Additionally, the cadmium ion-mediated changes in the biofilm composition affected the colonization of the strain on the host plant root surface. Cadmium ions also induced surfactin synthesis. These findings illustrate the potential of Bacillus species as biocontrol strains that can mitigate plant pathogenic infections and heavy metal stress. The results also provide a basis for the screening of multifunctional biocontrol strains.